Analysis of the Influence of the Construction of the Lolak Dam on Flood Disasters in the Lower Reaches of the Lolak River, Bolaang Mongondow Regency - Maramis, Anastasya Amelia; Riogilang, Herawaty; Thambas, Arthur Harris (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Flooding is one of the disasters that often hit the Lolak Watershed (DAS) area and caused considerable losses. This study aims to evaluate the Lolak Dam in reducing flood risk in downstream areas through a hydraulic modeling approach and develop a flood forecasting model that is able to map flood areas in order to support flood control efforts. The data used include river topography, dam technical data and flood discharge data for 5, 25, 50 and 100 years which are then analyzed using HEC-RAS software version 5.0.7 and the output is input for the preparation of potential flood inundation maps. The results of the study show that the Lolak Dam is able to reduce the water level and reduce the area affected by flooding downstream. In addition, the model is used as in the preparation of hazard maps, vulnerability maps and flood risk maps. This research makes an important contribution to disaster mitigation planning and water resource management based on spatial data and hydraulic simulation.